HTLV‐1 infection altered expression of CCR2, CXCR2, eNOS genes, and oxidative stress in aorta and heart of male mice - Saeed Niazmand; S. A. Rahim Rezaee; Jamshid Gholizadeh Navashenaq; Nema Mohamadian Roshan; Mohsen Ghoryani; Houshang Rafatpanah; Maryam Mahmoudabady; Yousef Baghcheghi; Maryam Paseban; Mahdiyeh Hedayati‐Moghadam (Physiological Reports)
Abstract Viral infections are associated with the disruption of oxidative stress and the progression of inflammatory mechanisms that play pivotal roles in cardiovascular diseases. In the present study, several inflammatory and oxidative stress markers were examined in HTLV‐1‐infected male BALB/c mice. Twenty BALB/c mice were divided into two groups: the HTLV‐1‐infected group and the control group. Two months later, samples were collected from blood, aorta, heart, spleen, and lymph nodes. Finally, the levels of various plasma markers (lipid profile, creatine phosphokinase, nitric oxide, GSH, and total thiol), oxidative stress markers (SOD and CAT activity, MDA and total thiol levels), chemokine receptors genes expression (CCR2, CXCR2, CCR1) and eNOS expression in aortic and heart tissues, as well as histopathological changes in the heart, were evaluated. Plasma triglyceride, creatine phosphokinase, nitric oxide, and aorta malondialdehyde levels in the HTLV‐1‐infected group were higher than those in the control group. In contrast, total thiol levels in plasma, heart, and aorta, plasma glutathione levels, and the activities of superoxide dismutase and catalase were lower compared to the control group. The expression of CCR2 and CXCR2 was elevated in the aorta of the HTLV‐1‐infected group, while eNOS expression was reduced in both aortic and heart tissues. HTLV‐1 may contribute to inflammatory responses and oxidative stress in cardiovascular tissues.